2016
DOI: 10.1128/mcb.00281-16
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Immune Deficiency in zap70 Mutant Zebrafish

Abstract: j ZAP70 [zeta-chain (TCR)-associated protein kinase, 70-kDa], is required for T cell activation. ZAP70 deficiencies in humans and null mutations in mice lead to severe combined immune deficiency. Here, we describe a zap70 loss-of-function mutation in zebrafish (zap70 y442 ) that was created using transcription activator-like effector nucleases (TALENs). In contrast to what has been reported for morphant zebrafish, zap70 y442 homozygous mutant zebrafish displayed normal development of blood and lymphatic vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Single radiation doses as low as 20 Gy or the administration of 25–250 µg/mL of dexamethasone are sufficient to ablate T cells [ 179 , 180 ]. Recently, immunocompromised transgenic lines have been created such as rag2(E450fs) and Tg(zap70 y442 ) [ 181 , 182 ]. The advantages of a transparent body, typical of the embryo stage, can also be maintained in adults.…”
Section: Zebrafish Xenograftsmentioning
confidence: 99%
“…Single radiation doses as low as 20 Gy or the administration of 25–250 µg/mL of dexamethasone are sufficient to ablate T cells [ 179 , 180 ]. Recently, immunocompromised transgenic lines have been created such as rag2(E450fs) and Tg(zap70 y442 ) [ 181 , 182 ]. The advantages of a transparent body, typical of the embryo stage, can also be maintained in adults.…”
Section: Zebrafish Xenograftsmentioning
confidence: 99%
“…And ADM is also a significant factor for worse survival in some cancers [49,50]. ZAP70 is related to the T cell antigen receptor (TCR) complex and is required for T cell activation [51,52]. RFXAP is a key transcription factor for major histocompatibility complex (MHC) II [53].…”
Section: Discussionmentioning
confidence: 99%
“…The main function of the enzyme is the regulation of intracellular signal transduction, especially immune signal transduction 31 . Amino acid sequence analysis indicated that SsPTK may perform special functions, and mutation may lead to immune cell defects 32 , 33 , making it a potential target for immunotherapy of mites.…”
Section: Discussionmentioning
confidence: 99%